A survey on the importance of the gold investment towards ACIS student UiTM Puncak Alam / Aina Madihah Mohd Nasir - Mohd Nasir, Aina Madihah (2019)
Students nowadays have less of awareness about the importance of gold investment that may cause problems later on. It is because they did not inform about the gold investment by others including family, friends, social media and society. The aims of this research are to identify knowledge level of students on gold investment and to analyse the importance of gold investment for the future among students. The questionnaire survey method used towards the Muamalat students of Academy of Islamic Contemporary (ACIS) at UiTM Puncak Alam. The findings of the research, majority of the respondents acknowledge about the gold and gold investment as they know about the value of gold, types of gold investment, gold physical, bank that offer gold investment, bank that practiced shariah compliance and the way of the profit that they can get from gold investment. The respondents also know about the important of gold investment, gold investment is a long-term investment, gold investment will increase the income, gold investment able to give higher return from appreciation, hedge against inflation, gold price is stable and less risk.